Berpikir Reflektif Siswa SMA dalam Menyelesaikan Masalah Geometri dari Gaya Belajar - Purwadhani, Dea Annice; Wijayanti, Pradnyo (MATHEdunesa, 2025)
Reflective thinking is one of the higher order thinking. Reflective thinking has not been fully realized during learning at school. This is due to the existence of a factor that influences one of them in terms of learning style. This research is a qualitative descriptive study that aims to describe the reflective thinking of high school students in solving geometry problems from visual, auditory, and kinesthetic learning styles. The research subjects were 3 students of each learning style and high math ability at SMA Negeri in Sidoarjo. Collecting data using tests, questionnaires, and interviews. Data were analyzed using indicators of reflective thinking contained in the four components of reflective thinking, namely selection of techniques, monitoring, insight, and conceptualization. The results of the study show that 1) students with a visual learning style have carried out all indicators on the reflective thinking component, namely selection of techniques, monitoring, conceptualization, and several indicators on the insight component, namely not checking and identifying wrong statements 2) students with an auditory learning style have carried out all indicators on the thinking component, namely monitoring and insight as well as several indicators on the selection of techniques and conceptualization components, namely not understanding the questions properly, not finding different strategies/alternatives to solve problems, and not connecting relevant experiences with problems 3) students with the kinesthetic learning style have carried out all a series of components of reflective thinking at once or the same as carrying out all the indicators totaling thirteen indicators of reflective thinking in it.